The Potential Integration of Informal to Formal Workers in Muara Fajar Landfill (TPA) Pekanbaru with the Circular Economy Concept - Rizky Syahputra; Gabriel Andari Kristanto; Astryd Viandila Dahlan (Jurnal Indonesia Sosial Teknologi, 2025)
Waste is a serious problem in developing countries due to infrastructure limitations, one of which is the city of Pekanbaru. The existence of the landfill triggered the arrival of informal workers such as scavengers to collect waste as recycled product materials. Most scavengers live below the poverty line, even though scavengers have a role in restraining the waste generation rate in landfills. This study aims to analyze the potential integration of scavengers in the Muara Fajar Landfill Area with formal workers using integrated waste management, "Clean Pekanbaru Movement." The research was conducted using observation methods, interviews, and questionnaires filled out by scavenger and collector respondents in the landfill area. The recycling rate (RR) of the Muara Fajar landfill area is 1.08%, and the average individual RR of 150 scavengers is 0.72%. The proposed integrated waste management concept is the "Clean Pekanbaru Movement," which manages the Muara Fajar landfill area and acts as a recycling industry player. The study results show that the recycling rate at the Muara Fajar landfill only reaches 1.08%, while the average individual scavenger only reaches 0.72%. The Pekanbaru Clean Movement model is proposed as a solution that integrates scavengers into a formal waste management system with regulatory support and the recycling industry. As many as 82% of respondents are willing to participate in this program for a fixed income and better social security. This study concludes that the potential for waste generation because of recyclable materials is still huge, and the potential for integration is very possible at the Muara Fajar Landfill, Pekanbaru. Implementing this program can improve the social welfare of scavengers and reduce the environmental impact due to the open waste disposal system.